(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Teacher–student interaction plays a crucial role in shaping learners’ speaking performance and emotional experiences in English for Specific Purposes (ESP) classrooms. Effective classroom interaction can encourage participation, increase confidence, and improve communicative competence, while negative interaction patterns may contribute to speaking anxiety and communication avoidance. The present study investigates how teacher–student interaction patterns influence ESP speaking performance among philology undergraduates. Using a qualitative research methodology, data were collected through classroom observations and semi-structured interviews conducted with undergraduate students enrolled in ESP programs. The findings reveal that supportive interaction patterns, collaborative communication, and respectful evaluative discourse positively affect students’ oral participation and speaking confidence. Conversely, teacher-centered interaction, excessive correction, and limited communicative opportunities negatively influence learners’ speaking performance and emotional well-being. The study emphasizes the importance of interactive, student-centered, and emotionally supportive teaching practices in promoting communicative competence in ESP education.